Ruthenium (II) and Platinum (II) Complexes of 4, 5, 6- Triaminopyrimidine; 2-Hydroxy-4, 5, 6-Triaminopyrimidine and uric Acid: Synthesis, Characterization and Physicochemical Studies - Suha Y. Nassar (Journal of Global Pharma Technology, 2018)
Six Ru(II) and Pt(II) of uric acid; 4,5,6-triaminopyrimidine and 2-hydroxy-4,5,6-triaminopyrimidine complexes were prepared and identified by elemental analysis, conductivity measurement, melting point records, U.V.-visible, FTIR, 1H-NMR, 13C-NMR and HSQC spectroscopy. Some physicochemical properties of the prepared complexes were studies such as their luminescence characters and nanonature, using XRD and SEM techniques. Four biological activities of these complexes, such as antibacterial, antioxidants and cytotoxic activities have been studied besides their interaction with bacterial DNA.